Microplastic contamination in brown shrimp (Crangon crangon, Linnaeus 1758) from coastal waters of the Southern North Sea and Channel area. Issue 1 (15th September 2015) - Devriese, Lisa I.; van der Meulen, Myra D.; Maes, Thomas; Bekaert, Karen; Paul-Pont, Ika; Frère, Laura; Robbens, Johan; Vethaak, A. Dick
Highlights: Crangon crangon living in natural habitats are able to ingest plastic particles. An average microplastics uptake of 0.68 ± 0.55/g w. w. was obtained for shrimp. A clear seasonal effect on the microplastic contamination in shrimp was established. Abstract: This study assessed the capability of Crangon crangon (L.), an ecologically and commercially important crustacean, of consuming plastics as an opportunistic feeder. We therefore determined the microplastic content of shrimp in shallow water habitats of the Channel area and Southern part of the North Sea. Synthetic fibers ranging from 200 μm up to 1000 μm size were detected in 63% of the assessed shrimp and an average value of 0.68 ± 0.55 microplastics/g w. w. (1.23 ± 0.99 microplastics/shrimp) was obtained for shrimp in the sampled area. The assessment revealed no spatial patterns in plastic ingestion, but temporal differences were reported. The microplastic uptake was significantly higher in October compared to March. The results suggest that microplastics >20 μm are not able to translocate into the tissues.